Spinal infarction caused by hypovolemic shock following massive bleeding from stab wounds to the neck. (February 2020) - Shibata, Tomoyoshi; Yoshimatsu, Hidehiko; Yano, Tomoyuki; Karakawa, Ryo; Ishikawa, Shinsuke; Takeda, Akira
Abstract: A 59-year-old female was brought to our emergency department with hypovolemic shock caused by massive bleeding from neck stab wounds inflicted by herself in a committed suicide. The patient complained of comparatively strong pain on her lower back and there was sensory and motor disturbance of bilateral lower limbs, but there was no trauma on the lumber region, the spine, or the vertebrae. After hemostasis, we performed magnetic resonance imaging, which demonstrated high intensity signal in the spinal and longitudinal area from the Th8 to the conus medullaris, and at center of the frontal horn on the upper thoracic spinal cord (owl's eye appearance) on T2 weighted images. This case was diagnosed as spinal infarction caused by low blood pressure as a result of massive bleeding. The basis of diagnosis were as follows: 1) an acute onset; 2) when the ambulance arrived, she was in hypovolemic shock caused by massive hemorrhage; 3) there was no trauma on the lumber region, the spine, or the vertebrae; 4) with CT taken on admission, aortic disease was not detected; and 5) she was not on any antipsychotic drugs which could cause thrombosis. We treated the patient following management protocol of cerebral infarction, but recovery of sensory and motor disorders was minimal.